2001
DOI: 10.1046/j.1463-1318.2001.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and classification of never operated and recurrent cryptoglandular fistulas‐in‐ano using hydrogen peroxide enhanced transanal ultrasound

Abstract: All never operated cryptoglandulair fistulas-in-ano were inter- or trans-sphincteric. An extra track was found in 5%. Recurrent fistulas-in-ano were supra or extrasphincteric in 15% and ramified in 27%. Therefore, never operated fistula-in-ano does not require any special investigation before surgical treatment. However, before treating recurrent fistulas, visualization by HPUS is recommended to detect supra or extrasphincteric fistulas or ramification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Probably we face the fact that many times pilonidal disease reminds perianal fistula (14)(15)(16). Some authors have reported 15% of sinuses in similar studies (6). In our opinion, this gives more value to endoanal ultrasound before surgery, as during surgery we can avoid useless and dangerous manipulations of the sphincters when trying to find a non-existant communication (13).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Probably we face the fact that many times pilonidal disease reminds perianal fistula (14)(15)(16). Some authors have reported 15% of sinuses in similar studies (6). In our opinion, this gives more value to endoanal ultrasound before surgery, as during surgery we can avoid useless and dangerous manipulations of the sphincters when trying to find a non-existant communication (13).…”
Section: Discussionmentioning
confidence: 98%
“…However, we could define it in more than 95% of patients when the external opening was open and the tract was related to the sphincters despite this being a biased series with a high number of specially complex fistulas (16.67% extra-sphincteric); it is still thought that only complex fistulas should be studied using ultrasounds (6). In our opinion, this high level of definite location of internal openings could be due to the explorer, who was always a general surgeon specialized in coloproctology and trained in this technique.…”
Section: Discussionmentioning
confidence: 99%
“…EUS combined with hydrogen peroxide (HPUS) as a contrast medium improves visualization and provides an accurate preoperative assessment of fistulas. [1][2][3][4][5] A new technique is three-dimensional (3D) EUS. 3D EUS enables axial images of the anal canal to be reconstructed in the coronal and sagittal planes.…”
mentioning
confidence: 99%
“…The accuracy of primary fistula diagnosis with unenhanced ultrasonography varies from 64% to 94%, with delineation of the internal opening in 28%-93% of cases and of horseshoe- 86 ing in 23%-81% of patients [18,[35][36][37][38][39][40][41][42][43]. Similar comparisons are made for enhanced EAUS, with reported rates for definition of the primary track and fistula anatomy ranging from 60% to 95%, delineation of the internal opening in 48%-94% of cases and horseshoeing in 75%-92% of patients [6,17,39,40,[44][45][46][47][48][49][50][51][52]. Comparative studies between enhanced and unenhanced ultrasonography suggested a significant advantage for the routine use of hydrogen peroxide in all these areas of fistula assessment [39-41, 48-50, 52] as well as in the distinction between linear and curvilinear tracks, a finding which has been suggested as being of some importance in sphincter preservation for recurrent complicated fistulae [53].…”
Section: Ultrasonographymentioning
confidence: 74%
“…Moreover, some have suggested that the suprasphincteric types of fistulae are most commonly iatrogenic in origin and not primarily cryptoglandular, resulting from injudicious probing of translevator tracks and extensions in those patients presenting with recurrent disease [15,16]. This view has been recently substantiated, where extra-and suprasphincteric fistulae were only identified in recurrently operated patients and not seen in those presenting with never operated cryptoglandular sepsis [17].…”
Section: Imaging Complex Perirectal Sepsis In Clinical Practicementioning
confidence: 99%